How Risk Attitudes Affect the Implementation of Good Agricultural Practices in Sugarcane Farming - Annisa Fauzia Astari; Irham Irham; Arini Wahyu Utami (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2019)
Indonesian Ministry of Agriculture issued Minister of Agriculture Regulations Number 53 in 2015 about Good Agricultural Practices for Sugarcane as an effort to increase production and productivity of sugarcane. The implementation of GAP on various commodities was differ since risk across commodities and risk attitude among farmers are varied. Hence, this study aims to analyze (1) the implementation level of Sugarcane GAP among farmers of the Wonolangan Sugar factory and (2) the influence of risk attitudes toward GAP implementation. The study was conducted on 102 randomly-selected farmers in Lumajang and Probolinggo Regency. The level of GAP implementation is measured by Likert scale with nine indicators of Sugarcane GAP. The level of GAP implementation is categorized into low, medium, and high based on the total score of GAP implementation obtained from each farmer. One-sample t-test is used to test the implementation level of GAP. Risk attitudes are measured with a Likert scale, as refers to Pennings and Garcia method. The influence of risk attitudes towards GAP implementation is analyzed using OLS regression. The result of t-test shows that the level of GAP implementation among sugarcane farmers is medium and high, and most farmers are risk-averse. Of the nine components used as indicators, seed preparation and labor welfare are in the medium category. Based on the OLS regression, risk-taker farmers have a lower GAP implementation than that of risk-averse farmers. Farmers' lack of knowledge about GAP guidelines, can be supported by the presence of socialization activities by sugar factories, extension workers, and related institutions.